Mesenchymal Stem Cell-Based Therapy for Lysosomal Storage Diseases and Other Neurodegenerative Disorders - Issa, Shaza S.; Shaimardanova, Alisa A.; Valiullin, Victor V.; Rizvanov, Albert A.; Solovyeva, Valeriya V. (Frontiers in Pharmacology, 2022)
Lysosomal storage diseases (LSDs) are a group of approximately 50 genetic disorders caused by mutations in genes coding enzymes that are involved in cell degradation and transferring lipids and other macromolecules. Accumulation of lipids and other macromolecules in lysosomes leads to the destruction of affected cells. Although the clinical manifestations of different LSDs vary greatly, more than half of LSDs have symptoms of central nervous system neurodegeneration, and within each disorder there is a considerable variation, ranging from severe, infantile-onset forms to attenuated adult-onset disease, sometimes with distinct clinical features. To date, treatment options for this group of diseases remain limited, which highlights the need for further development of innovative therapeutic approaches, that can not only improve the patients’ quality of life, but also provide full recovery for them. In many LSDs stem cell-based therapy showed promising results in preclinical researches. This review discusses using mesenchymal stem cells for different LSDs therapy and other neurodegenerative diseases and their possible limitations.